A Study on Socio-Economic Determinants and Economic Burden of Japanese Encephalitis in Kailali District of Nepal - Nepal Health Research Council (NHRC); Adhikari, Shiva Raj (Nepal Health Research Council, 2013)
Japanese encephalitis (JE) is emerging as a seriouspublic health problem in Nepal. The diagnosis and treatment of the JE patient has financial consequences to the society. An economic study on JE was conducted in a small area in Kailali district. The main objectives of the study were to: determine the sources and levels of incomeof the typical JE HH; measure the direct and indirect costs incurred by HH to obtain preventive,diagnostic and curative services to JE; identify the socio-economic factors responsible for JE transmission and suggest policy recommendations for prevention, control and treatment of JE. The study was based on primary as well as secondary sources. However, the study relied mainly on primary data. For primary data, 60 JE HHs, 30 male and 30 female, were randomly selected from the list ofJE patients from the hospital records. Pre-de signed, pre-tested questionnaires were administered, to collect quantitative information from the sampled HH. Focus group discussion with health personnel, JE patients, caretakers and key informants were also conducted to obtain in-depth information. Simple statistic al tools suchas averages, standard deviations, correlations between variables to explain the nature of relationship and test of significance have been used. DALY calculation has been made using the formula outlined by Murray.